Reasonable Magic and the Nature of Alchemy: Jewish Reflections on Human Embryonic Stem Cell Research - Zoloth, Laurie (Kennedy Institute of Ethics journal, 2002)
, The controversy about research on human embryonic stem cells both divides and defines us, raising fundamental ethical and religious questions about the nature of the self and the limits of science. This article uses Jewish sources to articulate fundamental concerns about the forbiddenness of knowledge in general and of knowledge thought of as magical creation. Alchemy, and the turning of elements into gold and into substances for longevity, and magic used for the creation of living beings was at stake in various Talmudic texts. Since contemporary discourse calls regenerative science magical, and makes claims about its restorative power, careful reflection on when magic is forbidden and when it is responsible allows a novel understanding of ethical questions in stem cell research.